Conversion of Design - Kapustin, Petr (project baikal, 2018)
In the diversity of meanings of the word ‘conversion’ one can notice new horizons of transformation of the activity, including architectural and design activity. To do this, it is necessary to clear the word of additional meanings and to comprehend its depth. While sharing Konstantin Lidin’s idea of the expected transformation of the architectural profession towards preservation of social-economic and cultural-environmental values, the author offers to discuss the boundaries and possibilities of this transformation.